Theoretical simulation of solid polymer electrolytes based on Poly(vinylidene fluoride) with lithium salts for lithium-ion battery application - Miranda, Daniel (2024)
Solid polymer electrolyte composited by poly(vinylidene fluoride) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) has been optimized for solid-state lithium-ion batteries taking into account the LiTFSI concentration. Computer simulations of battery systems was used to evaluate the influence of LiTFSI concentration at different battery operation temperatures (278.15 K, and 353.15 K) and different discharge rates (C/30 and 3C), evaluating also the dissipated ohmic heat. It is shown how battery performance depends on LiTFSI content, which is correlated with ionic mobility, diffusion and temperature. A minimum of 30% of LiTFSI content is essential to obtain suitable solid polymer electrolytes for battery operation.